2014
DOI: 10.1002/rnc.3199
|View full text |Cite
|
Sign up to set email alerts
|

Distributed robust control of uncertain linear multi‐agent systems

Abstract: SummaryIn this paper, the distributed H ∞  robust control problem synthesized with transient performance is investigated for a group of autonomous agents governed by uncertain general linear node dynamics. Based on the relative information between neighboring agents and some information of other agents, distributed state‐feedback and observer‐type output‐feedback control protocols are designed and analyzed, respectively. By using tools from robust control theory, conditions for the existence of controllers for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…Han et al investigate the robust consensus problem for multi‐agent systems with continuous‐time and discrete‐time dynamics in , where the weighted adjacency matrix is a polynomial function of uncertain parameters. In particular, the H ∞ robust control problem is investigated in for a group of autonomous agents governed by uncertain general linear node dynamics. However, most of the existing results on consensus control of uncertain multi‐agent systems were often restricted to certain conditions, like single or double integrators , undirected network connections or systems without delays .…”
Section: Introductionmentioning
confidence: 99%
“…Han et al investigate the robust consensus problem for multi‐agent systems with continuous‐time and discrete‐time dynamics in , where the weighted adjacency matrix is a polynomial function of uncertain parameters. In particular, the H ∞ robust control problem is investigated in for a group of autonomous agents governed by uncertain general linear node dynamics. However, most of the existing results on consensus control of uncertain multi‐agent systems were often restricted to certain conditions, like single or double integrators , undirected network connections or systems without delays .…”
Section: Introductionmentioning
confidence: 99%
“…From (17), it is found that the disturbance from leader has nothing to do with , which converges to zero exponentially with a speed faster than , if is derived by Theorem 1. Furthermore, we have:…”
Section: Proofmentioning
confidence: 78%
“…The decoupling property of Eq. (6) can be easily utilized to design distributed controllers, which has already been studied by many existing literature, for example [15] and [17]. When the topology is more generic, i.e., is a real matrix, its eigenvalues may be complex and repeated.…”
Section: Structural Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Lemma 3: [37]: For X T = X ∈ ℝ N × N and ∀Σ satisfying | | Σ | | ∞ ≤ 1, X + DΣR + DΣR T < 0, if and only if ∃ε > 0 ∈ ℝ, such that X + εDD T + ε −1 R T R < 0. Lemma 4: [36]: There exist R T = R ∈ ℝ N × N , D T = D ∈ ℝ N × N and λ, λ¯∈ ℝ, then ∀λ ∈ λ, λ¯, R + λD < 0 holds if and only if R + λ¯D < 0 and R + λD < 0.…”
Section: Lemmasmentioning
confidence: 99%